2017
DOI: 10.1016/j.jjcc.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Association between right ventricular systolic function and electromechanical delay in patients with right bundle branch block

Abstract: Prolonged R' wave duration in lead V1 is an indicator of RV dysfunction and pressure and/or volume overload in patients with RBBB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Furthermore, it has been demonstrated that ECG parameters of right ventricular conduction delay correlate with echocardiographic parameters of right ventricular systolic function. 13 In this cohort of patients with Eisenmenger syndrome, we demonstrated a significant correlation between the presence of right bundle branch block and SCD (2.4-fold increased risk; P=0.01). Mechanistically, right ventricular pressure or volume overload places strain on the right bundle and the associated Purkinje network, which travel subendocardially on the right ventricular septum; therefore, the presence of a right bundle branch block can herald right ventricular strain and subsequently contribute to further worsening of the right ventricular systolic function by altered hemodynamics, dyssynchrony, delayed opening of the pulmonary valve, and inefficient right ventricular emptying.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, it has been demonstrated that ECG parameters of right ventricular conduction delay correlate with echocardiographic parameters of right ventricular systolic function. 13 In this cohort of patients with Eisenmenger syndrome, we demonstrated a significant correlation between the presence of right bundle branch block and SCD (2.4-fold increased risk; P=0.01). Mechanistically, right ventricular pressure or volume overload places strain on the right bundle and the associated Purkinje network, which travel subendocardially on the right ventricular septum; therefore, the presence of a right bundle branch block can herald right ventricular strain and subsequently contribute to further worsening of the right ventricular systolic function by altered hemodynamics, dyssynchrony, delayed opening of the pulmonary valve, and inefficient right ventricular emptying.…”
Section: Discussionmentioning
confidence: 57%
“…Mechanistically, right ventricular pressure or volume overload places strain on the right bundle and the associated Purkinje network, which travel subendocardially on the right ventricular septum; therefore, the presence of a right bundle branch block can herald right ventricular strain and subsequently contribute to further worsening of the right ventricular systolic function by altered hemodynamics, dyssynchrony, delayed opening of the pulmonary valve, and inefficient right ventricular emptying. 13 Prolongation of the QRS interval was significantly associated with mortality, both sudden death and cardiac mortality. Furthermore, a QRS interval ≥120 ms predicted a 2.34-fold increased risk of SCD (P=0.009).…”
Section: Discussionmentioning
confidence: 99%
“…However, RS time prolongation was significantly associated with RV dysfunction. In addition to the prominence of superiorly and rightward-oriented late vectors in RV dysfunction, RV strain due to RV dysfunction may have caused a conduction delay in the ECG and altered the QRS complexes through structural changes in the myocardium [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…An increment in right ventricular afterload and strain is anticipated as a result of an increase in the resistance of pulmonary vasculature due to hypoxia. The right ventricular strain may cause a conduction delay in ECG and may also change the QRS complexes through structural alterations in the myocardium 22,27 . Logically, RS time tends to increase as the anatomical and functional abnormalities of the right ventricle become more prominent as the pulmonary function becomes more impaired.…”
Section: Discussionmentioning
confidence: 99%